Decomposition rate of pulverized oil palm trunk mulch within thirteen months - Ismail, Nurul Hidayah (2015)
Oil Palm Trunk (OPT) is one of the main waste products from the palm oil industry. After 20-25 years of oil palm growth, the replanting of old oil palm need to be conducted. This is to enhance the yield of oil palm as the yield decreases with age. There are several ways to conduct the oil palm that are felled. Before the banning of open burning under Malaysian Environmental Air Quality Regulation in 1978, the most common method of clearing old oil palms for replanting in Malaysia was the “chip and burn” method. This method can contribute to global warming and air pollution. With the ban on open burning, new alternative method management known as “chip and windrowed” was introduced. But this method can lead to a problem such as breeding of the Oryctes rhinoceros beetle. Apart from that, it is also as source of rat and Ganoderma boninense disease development cause by low sanitation. This project was conducted to investigate the decomposition rate of the pulverized OPT mulch, nutrient content and rate of nutrient release to the soil using pulverized machine. This research was continued from the previous project which had started from May (2013) and continued from January until September (2014). This decomposition process of pulverized oil palm trunk mulch took about 16 months. This project was conducted at UPM palm oil area (GPS: N 2 ° 58.826 E 101 ° 43.699) near the UPM Stadium. OPT sample which was about 7 kg was taken from Ladang Kota Bharu which is under the management of Trunkbuster Company at Kota Bharu, Gopeng, Perak (GPS : N 4 ° 23.352 E 101 ° 04.606) and was placed on soil in a tray. Munchong soil series were used, Completely Randomized Design (CRD) plot with 8 experimental units was used (4replication X 2 treatment). T1 treatment was the pulverized oil palm trunk mulch while T2 treatment (without use of pulverized oil palm trunk mulch) as a control. Only T1 treatment was be focused on this experiment because the need to measure of the characteristics and rate of decomposition of oil palm trunk mulch. For every month, samples were taken and nutrient content were analyzed by wet ashing method. The percentage of total nutrient remaining for Nitrogen are (80.9%), Calcium (19.54), Carbon (17.6%), Phosphorus (16.8%), Magnesium (7.8%), and Potassium (3.75%). The rate of decomposition are slow which was 0.109 (percentage remaining per month).